RESPON SISWA TERHADAP PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN HIGHER ORDER THINKING SKILLS - Imelda Imelda; Dewi Anzelina (MES: Journal of Mathematics Education and Science, 2019)
Abstract. The purpose of this study was to describe student responses to Problem Based Learning (PBL) learning in improving Higher Order Thinking Skills for students of SMP Negeri 4 Binjai. This type of research is descriptive research. The research subjects were 30 students of SMP Negeri 4 Binjai with a composition of 12 men and 18 women. The data analysis technique used a non-test technique, namely the student response questionnaire. Student responses were said to be positive towards PBL learning seen from four aspects namely feeling happy about the learning component, the novelty of the learning component used, students interested in participating in PBL learning activities, and interested in language, written appearance, teacher illustrations and the location of the images contained in the LAS. The results of the study are students giving a positive response to PBL learning shown by students happy with the PBL learning component, the PBL learning component used is new, students are interested in participating in PBL learning activities, and are interested in language, written appearance, teacher illustrations and the location of the images contained on LAS.Keywords: Problem Based Learning, Response, HOTS.